RUANG MENTAL DAN MODEL KOGNITIF IDEAL PEJABAT PEMERINTAH PADA HUMOR SATIRE #LORDLUHUT - Nurul Azizah (PRASASTI: Journal of Linguistics, 2022)
This research aims to (1) explain the relationship between the mental space of humor and #LordLuhut's satire; (2) describes the ideal concept of the idealized duties and authorities of government officials through the satire humor of #Lord Luhut. Citizen have the right to express their opinions and aspirations. There are many ways that can be done to convey the aspirations of a community to the government. One of them is by using social media to aspire their voice as a citizen. Criticism is conveyed through linguistic expressions on social media, one of which is manifested in satire humor. The data of this research is a form of humorous satire #LordLuhut which comes from various Twitter uploads. Data analysis was carried out qualitatively by using cognitive linguistic theories, such as mental space, profiling, prototypes and ideal cognitive models. The research results are presented with formal and informal methods. Several conclusions were obtained: (1) the existence of mental space in the expression of satire humor indicates that the expression is only imagination, not reality; (2) there is an ideal concept of a government official written by the author in the humorous satire #LordLuhut.